6H scratch-resistant acrylic plate as well as preparation method and application thereof

Through the lamination process and the hard coating of specific components, the wear resistance and toughness of acrylic plate materials are solved, the production process is simplified, the hardness and scratch resistance of acrylic plates are improved, and the hardness and scratch resistance of acrylic plates are improved, making it suitable for large-scale industrial production.

CN119144035AInactive Publication Date: 2024-12-17ZHEJIANG LIXINGDE TECH CO LTD

Patent Information

Application Number
CN202411643530.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing acrylic sheet materials have problems such as wear resistance, low toughness and complex preparation processes, which affect their quality and appearance, and the production costs of traditional processes are high, and the environment and workers' health are affected.

Method used

The lamination process is adopted to form a hardened coating layer with high hardness through components such as polyurethane acrylic resin, active monomers, metal oxide nanoparticles and photoinitiators, simplify the production process, reduce the coating and slitting process, and improve the level of automation.

Benefits of technology

6H scratch-resistant acrylic plates with high strength, wear resistance, high toughness and few defects are achieved, reducing production costs, improving production efficiency and product flatness, enhancing scratch-resistant performance, and reducing the impact on the environment and workers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144035A_ABST
    Figure CN119144035A_ABST
Patent Text Reader

Abstract

The invention discloses a 6H scratch-resistant acrylic plate as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. The acrylic plate comprises a first hardening coating, a PMMA (polymethyl methacrylate) layer and a second hardening coating from top to bottom. The scratch-resistant acrylic plate provided by the invention adopts an innovative hard liquid composition, and comprises polyurethane acrylic resin, an active monomer, metal oxide nanoparticles, a photoinitiator and an auxiliary agent. Compared with an existing scratch-resistant coating material, the scratch-resistant coating material has the advantages that the polyurethane acrylic resin is used as a main film forming substance and is combined with the active monomer and the photoinitiator, so that a high-hardness coating can be quickly formed under a photocuring condition, the formula of the coating is simplified, and the wear resistance, the toughness and the optical performance of the coating are effectively improved; the composition avoids dependence on traditional hardeners and solvents, reduces emission of volatile organic compounds, and is more environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and more particularly to a 6H scratch-resistant acrylic plate and a preparation method thereof. Background Art

[0002] Acrylic is a chemical material, the chemical name is "PMMA", which belongs to the polyacrylate class, also known as specially treated organic glass, and is a replacement product for organic glass. In the application industry, the raw materials of acrylic generally appear in the form of particles, plates, pipes, etc. It includes monomers, plates, granules, resins and composite materials. Acrylic plates are polymerized from methyl methacrylate monomers, that is, polymethyl methacrylate plates organic glass. Acrylic plates have the reputation of "plastic glass", have strong corrosion resistance, and have strong surface hardness and gloss. Acrylic plates have crystal-like transparency, light transmittance of more than 92%, soft light, clear vision, and acrylic colored with dyes has a good color development effect.

[0003] Acrylic sheets have excellent weather resistance, high surface hardness and surface gloss, and good high temperature performance. Transparent acrylic sheets have a transmittance comparable to glass, but the density is only half of that of glass. In addition, it is not as fragile as glass, and even if it breaks, it will not form sharp fragments like glass. Therefore, the application of acrylic sheets is becoming more and more extensive, especially in the fields of construction, advertising, etc. With the development and progress of society, more and more acrylic sheets have begun to enter all walks of life and have made great contributions.

[0004] However, although acrylic has a high hardness, compared with other existing polymer sheets, existing acrylic sheet materials are usually accompanied by problems such as poor wear resistance, low toughness and obvious defects. In addition, existing acrylic sheet production lines have certain defects such as complex preparation processes and low automation, which affect the quality and appearance of acrylic sheets.

[0005] In response to the relevant problems, CN106633573A prepares a scratch-resistant acrylic sheet with the advantages of high strength, wear resistance, high toughness and few defects by combining acrylic with petroleum resin, vinyl acetate fiber, asbestos fiber, silicon carbide fiber, potassium aluminum silicate, nanocellulose, lignin, glass beads, quartz powder, methacrylic acid chloride complex, carbonate, xylene, zirconium titanate, scratch-resistant additives and other ingredients. However, the material preparation process involves related casting procedures. Compared with other preparation processes such as lamination, there are problems such as high production cost, a certain irritating odor will be generated during the production process, relatively large impact on the environment and workers' health, and not conducive to large-scale production. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a 6H scratch-resistant acrylic sheet with high strength, wear resistance, high toughness and few defects through lamination and related technologies, and to explain the relevant production method and production line.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A 6H scratch-resistant acrylic plate comprises, from top to bottom, a first hard coating layer, a PMMA layer and a second hard coating layer.

[0009] Preferably, the first hard coating layer and the second hard coating layer both include the following components by mass percentage: 20-60% polyurethane acrylic resin, 5-30% active monomer, 0.5-2% metal oxide nanoparticles, <10% photoinitiator, and the rest are auxiliary agents.

[0010] Preferably, the PMMA layer comprises the following components by mass percentage: 0.8-1.2% toughening agent, 0.2-0.7% UV inhibitor, and the balance being polymethyl methacrylate particles.

[0011] Preferably, the active monomer is a silane coupling agent;

[0012] The metal oxide nanoparticles are niobium pentoxide, cerium dioxide or titanium dioxide whose surfaces are treated with hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride;

[0013] The photoinitiator is azobisisobutyronitrile;

[0014] The auxiliary agent is ethanol.

[0015] Preferably, the toughening agent is silicon dioxide nanoparticles;

[0016] The anti-UV agent is UV-P.

[0017] Another object of the present invention is to provide a method for preparing the above-mentioned 6H scratch-resistant acrylic sheet, comprising the following steps:

[0018] (1) Raw material preparation

[0019] The toughening agent, the anti-UV agent and the polymethyl methacrylate particles are dried to remove the moisture contained in the raw materials;

[0020] (2) High temperature melting

[0021] The raw materials are conveyed into the screw cavity and heated by the automatic feeding system, so that the raw materials are fully melted at high temperature;

[0022] (3) Extrusion

[0023] The melted liquid is extruded evenly by adjusting the metering pump speed to 20-40 rpm, and the thickness of the sheet is controlled to be 2.0 mm;

[0024] (4) Cooling into plate

[0025] By adjusting the roller speed, the product is quickly cooled and formed at room temperature, so that the plate can be quickly cooled and kept flat;

[0026] (5) Coating of hardening liquid and its drying and curing

[0027] Apply hardening liquid on the surface of the board, and then dry it at 60℃ for 4h to form a hardening coating to increase the surface hardness of the product;

[0028] (6) Lamination, slitting and packaging

[0029] A PE protective film is attached to the surface of the sheet, and after slitting and packaging, the final 6H scratch-resistant acrylic sheet is obtained.

[0030] Preferably, the drying in step (1) is performed at 75° C. for 4 hours.

[0031] Preferably, the heating temperature in step (2) is 190-260°C.

[0032] Preferably, the thickness of the hard coating layer is 50 μm.

[0033] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0034] The current existing processing technology is usually divided into two sections. The first part is the production of acrylic center board, and the relevant steps include raw material preparation, high temperature melting, extrusion, cooling molding, laminating, slitting and packaging. The second part is the surface hardening process of acrylic center board, and the relevant steps include film tearing, coating, drying and curing, laminating, slitting and packaging. The relevant processing flow is relatively complicated, which directly affects the cost of the product. In addition, there are still a small number of patent reports, such as CN106633573A on scratch-resistant acrylic, which is composed of raw materials polymethyl methacrylate, petroleum resin, vinyl acetate fiber, asbestos fiber, silicon carbide fiber, potassium aluminum silicate, nanocellulose, lignin, glass beads, quartz powder, chromium chloride complex of methacrylate, iodate, xylene, titanate and scratch-resistant additives. However, the relevant components need to be blended with acrylic (polymethyl methacrylate), and the components are relatively complex and the cost is high. The present invention has made certain improvements in the production process. By using a specific process and a hardening liquid with specific ingredients, the two steps of producing the acrylic center board and the acrylic center board surface hardening process are combined and improved into one step, thereby achieving innovation in the relevant production process, reducing the lamination, slitting and packaging of the acrylic center board, and the film tearing process in the subsequent hardening process, thereby greatly reducing the complexity of the production process.

[0035] The preparation method of the present invention not only reduces the need for manual operation and equipment, but also improves the automation level of the production line, significantly improving production efficiency and being suitable for large-scale industrial production. In addition, by simplifying the process, the present invention also reduces product defects caused by multi-step operations, such as surface defects caused by film tearing, making the surface of the finished product smoother and more uniform, and further enhancing the anti-scratch performance;

[0036] The scratch-resistant acrylic sheet of the present invention adopts an innovative hard liquid composition, including polyurethane acrylic resin, active monomers, metal oxide nanoparticles, photoinitiators and additives. Compared with existing scratch-resistant coating materials, the present invention uses polyurethane acrylic resin as the main film-forming substance, combined with active monomers and photoinitiators, and can quickly form a high-hardness coating under photocuring conditions, which not only simplifies the coating formula, but also effectively improves the wear resistance, toughness and optical properties of the coating. The added semiconductor nanomaterials such as niobium pentoxide and cerium dioxide, and the related additives have anti-ultraviolet and antibacterial components, so that the present invention can achieve certain anti-ultraviolet and antibacterial properties. In addition, this composition avoids dependence on traditional hardeners and solvents, reduces the emission of volatile organic compounds, and is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0038] Figure 1 This is a structural diagram after the hard coating layer of the present invention is applied;

[0039] Figure 2 It is a process flow chart of the present invention;

[0040] Figure 3 This is a microscopic morphology characterization diagram of the product of the present invention;

[0041] Figure 4 This is a friction coefficient detection diagram of the present invention;

[0042] Figure 5 This is the Fourier infrared spectrum detection diagram of the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] This embodiment provides a 6H scratch-resistant acrylic plate, which includes, from top to bottom: a first PE protective film, a first hard coating layer, a PMMA layer, a second hard coating layer, and a second PE protective film.

[0046] In this embodiment, the first hard coating layer and the second hard coating layer include the following components by mass percentage: 60% polyurethane acrylic resin, 25% silane coupling agent, 2% niobium pentoxide with surface treated with hexadecyltrimethylammonium bromide, 8% azobisisobutyronitrile, and 5% ethanol.

[0047] The PMMA layer includes the following components by mass percentage: 1.2% of silicon dioxide nanoparticles, 0.2% of UV-P, and the balance of polymethyl methacrylate particles.

[0048] Example 2

[0049] This embodiment provides a 6H scratch-resistant acrylic plate, which includes, from top to bottom: a first PE protective film, a first hard coating layer, a PMMA layer, a second hard coating layer, and a second PE protective film.

[0050] In this embodiment, the first hard coating layer and the second hard coating layer include the following components in percentage by mass: 59.5% polyurethane acrylic resin, 30% silane coupling agent, 0.5% cerium dioxide whose surface is treated with hexadecyltrimethylammonium chloride, <5% azobisisobutyronitrile, and <5% ethanol.

[0051] The PMMA layer includes the following components by mass percentage: 1.2% of silicon dioxide nanoparticles, 0.7% of UV-P, and the balance of polymethyl methacrylate particles.

[0052] Example 3

[0053] This embodiment provides a 6H scratch-resistant acrylic plate, which includes, from top to bottom: a first PE protective film, a first hard coating layer, a PMMA layer, a second hard coating layer, and a second PE protective film.

[0054] In this embodiment, the first hard coating layer and the second hard coating layer include the following components by mass percentage: 30% polyurethane acrylic resin, 10% silane coupling agent, 1% titanium dioxide with surface treated with hexadecyltrimethylammonium bromide, 8% azobisisobutyronitrile, and 51% ethanol.

[0055] The PMMA layer includes the following components by mass percentage: 0.8% silicon dioxide nanoparticles, 0.7% UV-P, and the balance polymethyl methacrylate particles.

[0056] Example 4

[0057] This embodiment provides a method for preparing the 6H scratch-resistant acrylic sheet in Embodiments 1-3, comprising the following steps:

[0058] (1) Raw material preparation

[0059] The toughening agent, the anti-UV agent and the polymethyl methacrylate particles were dried at 75°C for 4 hours to remove the moisture contained in the raw materials;

[0060] (2) High temperature melting

[0061] The raw materials are conveyed into the screw cavity through the automatic feeding system and heated to 225°C to fully melt the raw materials at high temperature;

[0062] (3) Extrusion

[0063] The melted liquid was extruded evenly by adjusting the metering pump speed to 30 rpm, and the thickness of the sheet was controlled to be 2.0 mm;

[0064] (4) Cooling into plate

[0065] By adjusting the roller speed, the product is quickly cooled and formed at room temperature, so that the plate can be quickly cooled and kept flat;

[0066] (5) Coating of hardening liquid and its drying and curing

[0067] Apply hardening liquid on the surface of the board, and then dry it at 60℃ for 4h to form a hardening coating with a thickness of 50μm to increase the surface hardness of the product;

[0068] (6) Lamination, slitting and packaging

[0069] A PE protective film is attached to the surface of the sheet, and after slitting and packaging, the final 6H scratch-resistant acrylic sheet is obtained.

[0070] Microscopic morphology characterization:

[0071] See also Figure 3 The microscopic morphology of the material surface was observed through a metallographic microscope. It can be seen from the microscopic morphology diagram that the 6H scratch-resistant acrylic plate provided by the present invention has a relatively smooth surface and still has a small amount of defects.

[0072] Hardness test:

[0073] The microhardness was measured using a Vickers hardness tester with a load of 10 g and a dwell time of 15 s. The average value of 5 locations was selected to determine the microhardness value of each sample.

[0074] The hardness value of the present invention is measured to be 72.62 HV 0.01 Compared with the hardness of the untreated acrylic laminate of 52.12 HV0.01, it can be seen that the hardness is significantly improved after treatment.

[0075] In addition, the surface hardness was tested according to the national standard GB / T 6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes", and the product of the present invention can achieve a hardness of 6H.

[0076] Wear test:

[0077] The samples were subjected to dry sliding wear tests using a high-speed reciprocating friction and wear tester. Under a load of 10 N, the samples were rubbed with a GCr15 grinding ball with a diameter of 6 mm at a sliding speed of 500 t / min for 30 min, and the wear track length was kept at 5 mm. Then, the profile of the wear track was obtained using a surface profiler. The value of the wear volume (V) was obtained by the following formula:

[0078] V = S l

[0079] Where l is the length of the wear track (5 mm), and S is the area adjacent to the wear track under the initial surface, which can be obtained from the cross section of the wear track. The wear rate (K) can be calculated by the formula:

[0080] K=V / (F·L)

[0081] Where F is the normal load (10 N) and L is the total sliding length (150 m).

[0082] After calculation, the wear rate of the modified steel is k = 5.55×10 -5 mm 3 / Nm, compared with the plate without surface treatment, the wear rate k = 4.5×10 -4 mm 3 / Nm. It can be seen that the wear rate is significantly reduced after treatment, achieving the anti-scratch effect.

[0083] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0084] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A 6H scratch-resistant acrylic sheet, characterized in that: From top to bottom, it includes: a first hard coating layer, a PMMA layer and a second hard coating layer.

2. A 6H scratch-resistant acrylic sheet according to claim 1, characterized in that: The first hard coating layer and the second hard coating layer both include the following components by mass percentage: 20-60% polyurethane acrylic resin, 5-30% active monomer, 0.5-2% metal oxide nanoparticles, <10% photoinitiator, and the rest are auxiliary agents.

3. The 6H scratch-resistant acrylic sheet according to claim 1, characterized in that: The PMMA layer comprises the following components by mass percentage: 0.8-1.2% of a toughening agent, 0.2-0.7% of an anti-UV agent, and the remainder being polymethyl methacrylate particles.

4. The 6H scratch-resistant acrylic sheet according to claim 2, characterized in that: The active monomer is a silane coupling agent; The metal oxide nanoparticles are niobium pentoxide, cerium dioxide or titanium dioxide whose surfaces are treated with hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride; The photoinitiator is azobisisobutyronitrile; The auxiliary agent is ethanol.

5. The 6H scratch-resistant acrylic sheet according to claim 3, characterized in that: The toughening agent is silicon dioxide nanoparticles; The anti-UV agent is UV-P.

6. A method for preparing a 6H scratch-resistant acrylic sheet as claimed in claim 4 or 5, characterized in that: The following steps are involved: (1) Raw material preparation The toughening agent, the anti-UV agent and the polymethyl methacrylate particles are dried to remove the moisture contained in the raw materials; (2) High temperature melting The raw materials are conveyed into the screw cavity and heated by the automatic feeding system, so that the raw materials are fully melted at high temperature; (3) Extrusion The melted liquid is extruded evenly by adjusting the metering pump speed to 20-40 rpm, and the thickness of the sheet is controlled to be 2.0 mm; (4) Cooling into plate By adjusting the roller speed, the product is quickly cooled and formed at room temperature, so that the plate can be quickly cooled and kept flat; (5) Coating of hardening liquid and its drying and curing Apply hardening liquid on the surface of the board, and then dry it at 60℃ for 4h to form a hardening coating to increase the surface hardness of the product; (6) Lamination, slitting and packaging A PE protective film is attached to the surface of the sheet, and after slitting and packaging, a 6H scratch-resistant acrylic sheet is obtained.

7. The method for preparing a 6H scratch-resistant acrylic sheet according to claim 6, characterized in that: The drying in step (1) is performed at 75° C. for 4 h.

8. The method for preparing a 6H scratch-resistant acrylic sheet according to claim 6, characterized in that: The heating temperature in step (2) is 190-260°C.

9. The method for preparing a 6H scratch-resistant acrylic sheet according to claim 6, characterized in that: The thickness of the hard coating layer was 50 μm.

10. Use of the 6H scratch-resistant acrylic sheet as claimed in claim 4 or 5 in building materials, furniture and decorations.

Citation Information

Patent Citations

  • Transparent functional membrane containing functional ultrafine particles, transparent functional film, and process for producing the same

    CA2412189A1

  • Ultraviolet-cured hard coating and application thereof

    CN102236113A

  • Printable hardened film formula suitable for different glue systems and printing film

    CN112708342A

Cited By

  • Acrylic hardening coating, preparation method thereof and acrylic product

    CN119799154A

  • An acrylic hardening coating, its preparation method and an acrylic product

    CN119799154B